PENERAPAN UANG PENGGANTI DALAM PERKARA TINDAK PIDANA KORUPSI (STUDI KASUS : PUTUSAN NOMOR 1046 K/PID.SUS/2017) (Lex Jurnalica, 2019)
AbstrakCorruption crimes in Indonesia have been very widespread and have come into the whole layer of community life. Its development continues to increase from year to year, in the number of cases and the amount of state financial losses as well as in terms of the quality of corruption that is carried out increasingly systematic that has entered all aspects of community life. Corruption acts are a violation of the social rights and economic rights of the community, so that the criminal acts of corruption are no longer classified as ordinary crimes but have become extraordinary crimes. So in an effort eradicationcan no longer be done on a regular basis, but it is demanded extraordinary ways.From the background above, it is the problem in the writing of this law that is how the arrangement of the types of punishment in the Corruption Act of law, as well as how the process of applying a substitute for money in criminal matters Case studies corruption verdict No. 1046 K/PID. SUS/2017. Considering this study uses a normative approach, the collection of legal materials is done by identifying and inventing procedures of primary legal materials and secondary legal substances and tertiary legal materials.The results showed that the main goal weighed the types of sanctions in the Criminal Acts of Corruption Lawis to provide a deterrent effect against the victims who have detrimental to the state in order to restore and restore the state's finances by paying Additional criminal in the form of substitute money and the replacement of the money in this case is very unwarranted, because the defendant is not proven to accept "gifts or promises". In this case the violated law is a corruption criminal act. Criminal law of corruption is one of the special criminal. The principle of its implementation is that special criminal law takes precedence over general criminal. Keywords: Corruption, Criminal acts,Substitute money, The replacement of the money. AbstrakKejahatan korupsi di Indonesia telah sangat luas dan telah memasuki seluruh lapisan kehidupan masyarakat. Perkembangannya terus meningkat dari tahun ke tahun, dalam jumlah kasus dan jumlah kerugian keuangan negara serta dari segi kualitas korupsi yang dilakukan semakin sistematis dan telah memasuki semua aspek kehidupan masyarakat. Tindakan korupsi adalah pelanggaran terhadap hak sosial dan hak ekonomi masyarakat, sehingga tindak pidana korupsi tidak lagi diklasifikasikan sebagai kejahatan biasa tetapi menjadi kejahatan luar biasa. Jadi dalam upaya pemberantasan tidak bisa lagi dilakukan secara rutin, tetapi dituntut cara yang luar biasa. Dari latar belakang di atas, masalah dalam penulisan ini adalah bagaimana pengaturan jenis-jenis hukuman dalam UU Tipikor, serta bagaimana proses penerapan pengganti uang dalam masalah pidana Studi kasus korupsi putusan No. 1046 K / PID. SUS / 2017. Penelitian ini menggunakan pendekatan normatif, pengumpulan bahan hukum dilakukan dengan mengidentifikasi dan menemukan prosedur bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Hasil penelitian menunjukkan bahwa sanksi dalam Undang-Undang Pidana Korupsi adalah untuk memberikan efek jera terhadap para korban yang merugikan negara,  dalam rangka mengembalikan dan mengembalikan keuangan negara dengan membayar tambahan, dalam bentuk uang pengganti dan penggantian uang, dalam kasus ini sangat tidak beralasan, karena terdakwa tidak terbukti menerima "hadiah atau janji". Dalam hal ini hukum yang dilanggar adalah tindak pidana korupsi. Hukum pidana korupsi adalah salah satu dari pidana khusus. Prinsip penerapannya adalah bahwa hukum pidana khusus lebih diutamakan daripada pidana umum. Kata kunci: Korupsi, Tindak Pidana, Uang pengganti, Penggantian uang.